PERANCANGAN PUSAT PERBELANJAAN MODERN DENGAN KONSEP CITYWALK DI KOTA GORONTALO - Zakir abdul rafiq goma; Zuhriati A. Djailani; Berni Idji (JAMBURA Journal of Architecture, 2020)
Modern shopping centers are one of the phenomena that occur in an area, both in big cities and small cities in Indonesia. The existence of a shopping center impacts the development of a city. Furthermore, the shopping center means a group of retailers and their other commercial activities that are planned, developed, owned, and operated in one unit.A modern Shopping Center with the Citywalk Concept is expected to meet the shopping and recreational needs of all Gorontalo people and tourists, who visitGorontalo. The design of this modern shopping center employed the Citywalk approach. Moreover, this gualitative research was carried out by reading the phenomena that arise in several cases in parts of city, especially in the transformation of areas with new developments inside.